2003
DOI: 10.1063/1.1543858
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of FePt and FePt–Al2O3 granular films by post annealing

Abstract: FePt and FePt–Al2O3 alloy thin films were prepared by rf magnetron sputtering system, then post annealed in vacuum. The as-deposited films were in disordered state and the ordered L10 structure was obtained by post annealing. The temperature for L10 structure of FePt and FePt–Al2O3 films was about 400 and 550 °C, respectively. The effect of film thickness on magnetic properties was studied. The coercivity decreased rapidly from 8 to 1.5 kOe at the thickness below 10 nm for the FePt L10 films. The decrease of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…As t decreases to 10 nm, the easy axis is perpendicular to the film plane. The decrease of the coercivity may be ascribed to the decrease of the anisotropy energy of the magnetic particles as the particle size decreases due to the decreasing t , which has been observed in the FePt‐based films 33–35. Meanwhile, the escape of the N atoms during the thermal annealing makes the diffusion of the Fe and Pt atoms easy, and when t is small the FePt grains will grow with preferred (001) orientation 36, so that the easy axis is perpendicular to the film plane.…”
Section: Resultsmentioning
confidence: 98%
“…As t decreases to 10 nm, the easy axis is perpendicular to the film plane. The decrease of the coercivity may be ascribed to the decrease of the anisotropy energy of the magnetic particles as the particle size decreases due to the decreasing t , which has been observed in the FePt‐based films 33–35. Meanwhile, the escape of the N atoms during the thermal annealing makes the diffusion of the Fe and Pt atoms easy, and when t is small the FePt grains will grow with preferred (001) orientation 36, so that the easy axis is perpendicular to the film plane.…”
Section: Resultsmentioning
confidence: 98%
“…Since the ordering process into the L1 0 phase is kinetically hindered, either post-deposition annealing [20] or layer by layer deposition of the Fe and Pt layers has to be performed at elevated temperatures [8,19,27]. As the magnetic properties are determined by the Fe-Pt interaction, the choice of the Fe and Pt layer thickness allows for tuning the magnetic properties (magnetisation orientation, K u ; thus the layer-by-layer deposition technique with adjustment of the individual layer thicknesses was utilised in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Many groups reported the addition of TaN, AlO x , MgO, Ti, Ag, and C to control FePt grain size in composite films. [6][7][8][9][10][11][12] Other studies have reported to incorporate a material such as Ni, BN, and SiO 2 to isolate the FePt particles and to reduce intergrain magnetic coupling. [13][14][15] The decoupling of intergranular interaction could decrease the medium noise and enhance the signal-tonoise ratio.…”
Section: Introductionmentioning
confidence: 99%